1996
DOI: 10.1159/000188804
|View full text |Cite
|
Sign up to set email alerts
|

Childhood IgM Nephropathy: Comparison with Minimal Change Disease

Abstract: The distinctiveness of IgM nephropathy (IgMN) as a clinicopathologic entity is controversial. Twenty-seven children (16 males, 11 females) with IgMN as defined immunohistochemically by diffuse mesangial staining of glomeruli for IgM were compared to a group of 63 children (40 males, 23 females) with minimal change disease (MCD). While mesangial expansion was significantly greater in IgMN than in MCD (p = 0.0014), there were no significant differences between the two groups with respect to the other biopsy fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 16 publications
(38 reference statements)
1
27
2
1
Order By: Relevance
“…It follows from various studies that IgMN responds less well to steroids compared to typical minimal change disease (MCD), and favours the hypothesis that IgMN is distinct from MCD [2,6] . Other researchers have not found any significant differences in clinical, pathological or steroid response pattern among these diseases [1,15] . The data on the use and response rates of immunosuppressive agents in paediatric IgMN is quite inadequate [2,22] .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It follows from various studies that IgMN responds less well to steroids compared to typical minimal change disease (MCD), and favours the hypothesis that IgMN is distinct from MCD [2,6] . Other researchers have not found any significant differences in clinical, pathological or steroid response pattern among these diseases [1,15] . The data on the use and response rates of immunosuppressive agents in paediatric IgMN is quite inadequate [2,22] .…”
Section: Discussionmentioning
confidence: 79%
“…Glomeruli show diverse grade of mesangial hypercellularity or no changes by light microscopy [1] . However, recent edition of Heptinstall's pathology of the kidney (7 TH edition) defines IgMN as cases with bright staining (at least two positive out of three) and with demonstrable mesangial deposits on electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of morphological changes in glomerular pathology range from mild to moderate mesangial proliferation in majority of the cases involving about 70-75%, followed by FSGS in 15-20% and unremarkable morphology/ MCD in 5-10% biopsies (11,(20)(21)(22)(23)(24)(25). (figure 1a).…”
Section: Pathology 331 Light Microscopymentioning
confidence: 99%
“…Most of the studies have reported the prevalence of the disease as frequency or percentage of renal biopsies with a diagnosis of IgMN. The frequency of IgMN reported in literature has varied considerably from 2% to 18.5% (Al-Eisa et al, 1996;Cavalo et al, 1981;Kazi et al, 2010;Kopolovic et al, 1987;Lawler et al, 1980;Mampaso et al, 1981;Cavalo & Johnson, 1981;Chan et al, 2000;Donia et al, 2000;Hsu et al, 1984;Jungthirapanich et al, 1997;Kobayashi et al, 1982;Mubarak et al, 2011;Singhai et al, 2011;Tejani & Nicastri, 1983). The first two pioneering studies found frequencies of 2 and 6.1% respectively in their biopsy series (Cohen et al, 1978;Bhasin et al, 1978).…”
Section: Epidemiologymentioning
confidence: 99%
“…Variable degrees of fusion of foot processes commensurate with the degree of proteinuria have also been observed. The electron-dense deposits have typically been of low volume and low density, and in many cases, rather ill-defined (Al- Eisa et al, 1996;Hsu et al, 1984;Myllimaki et al, 2003). …”
Section: Electron Microscopymentioning
confidence: 99%